Antioxidant Effects of Vitamin D on Lacrimal Glands against High Dose Radioiodine-Associated Damage in an Animal Model - Eksioglu, U.; Atilgan, H. I.; Yakin, M.; Yazihan, N.; Altiparmak, U. E.; Yumusak, N.; Korkmaz, M.; Demir, A.; Ornek, F.; Ayral, P. Aribal; Koca, G. (SPRINGER, 2018)
31st Annual Congress of the European-Association-of-Nuclear-Medicine (EANM), Dusseldorf, GERMANY, OCT 13-17, 2018